2013
DOI: 10.1007/s11605-013-2300-8
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Gastrosplenic Circulation and Splenic Function after Distal Pancreatectomy with Spleen Preservation and Splenic Vessel Excision

Abstract: Seven days after surgery, 63% of patients had some degree of splenic hypoperfusion, and 6 months after surgery, 83% of patients had normal perfusion. CT scans showed varices in 26 patients, and endoscopy revealed varicose veins in 11. Two patients experienced bleeding; markers of splenic hypofunction were found in 59% of cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 16 publications
1
12
1
Order By: Relevance
“…In contrast, Kohan et al reported that some degree of splenic hypoperfusion was observed at 1 week after the operation in 63% (22/35) of patients who underwent lap-WT (25). In the present study, although lap-WT induced a splenic infarction in 24% (4/17) of the patients, all of the infarctions were focal and none required splenectomy.…”
Section: Tien Et Al Reported That Postoperative Splenomegaly Followicontrasting
confidence: 87%
“…In contrast, Kohan et al reported that some degree of splenic hypoperfusion was observed at 1 week after the operation in 63% (22/35) of patients who underwent lap-WT (25). In the present study, although lap-WT induced a splenic infarction in 24% (4/17) of the patients, all of the infarctions were focal and none required splenectomy.…”
Section: Tien Et Al Reported That Postoperative Splenomegaly Followicontrasting
confidence: 87%
“…Spleen infarction did also occur in 8 (24%) patients with our robotic approach, and no adverse clinical consequence such as infarction‐related spleen abscess was observed. As shown in the literature and our study, most of these spleen infarctions are partial infarctions of less than 30%–50% of the spleen or hypoperfusion, and resolved spontaneously during the subsequent follow‐up period . Therefore, both gastric/perigastric varices, and spleen infarction after distal pancreatectomy with spleen preservation by the Warshaw technique, appeared to be clinically irrelevant.…”
Section: Discussionsupporting
confidence: 64%
“…Spleen infarction and gastric varices are two concerns after distal pancreatectomy with spleen preservation by the Warshaw technique. The rate of spleen infarction was reported to be 2%–74.3%, the rate of gastric varices 8.1%–52.5% and the rate of perigastric varices 25%–70% . However, they are usually asymptomatic during the post‐operative follow‐up period .…”
Section: Discussionmentioning
confidence: 99%
“…The numbers of HJB and WBC in the blood correlate with splenic function (21). HJB, WBC, neutrophils and lymphocytes were counted using a light microscope following Wright staining.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, when analyzing gene expression profiles in the spleen, we found 53 differentially expressed mRNAs in the mice in the depression model group, and two signaling pathways were more affected. A total of 11 of 53 differentially expressed genes in the spleen wre closely associated with depression, of which many differentially expressed genes were also screened in other experiments as differentially expressed genes in the brain (21). Based on these results, we can infer that the changes in the levels of genes in the spleen may also be one of the pathological mechanisms of depression.…”
Section: Discussionmentioning
confidence: 99%